HUBUNGAN KECERDASAN EMOSIONAL DENGAN HASIL BELAJAR BIOLOGI SISWA KELAS X MIA MAN 3 MEDAN T.P. 2017/2018 - Nur Aisyah Putri Rambe; Uswatun Hasanah; Neneng Chairunnisa (Universitas Negeri Medan, 2018)
This study aims to determine the relationship of emotional intelligence with learning outcomes Biology X class students MIA MAN 3 Medan Year Learning 2017/2018. The population in this study is all students of class X MIA MAN 3 Medan consisting of 5 classes. Sample used 2 classes from 5 classes with total 81 students. To obtain the data of emotional intelligence used questionnaire that has been validated by a validator lecturer. While the results of biology learning taken from the value of daily student ulagan obtained from teachers of Biology study. The data obtained are searched for the mean value, standard deviation, and test the data requirements. Emotional intelligence of students has ± SD of 91.30 ± 9.26, while the student's biology learning outcome is 78.37 ± 8.73. From the results of statistical analysis known the relationship of emotional intelligence with the results of biology students have a linear regression equation and have a meaningful relationship, this we can see from the high correlation coefficient of 0.871 and the amount of emotional intelligence contribution to student biology learning results of equal 75.69%. This means that emotional intelligence has a positive relationship with learning outcomes Biology X class student MIA MAN 3 Medan Year Learning 2017/2018.Keywords: Emotional intelligence, learning outcomes.